Humidity effect in heating and cooling of press‐formed paperboard food packages: Comparison of storing and heating conditions. Issue 8 (4th May 2021) - Niini, Arvo; Leminen, Ville; Tanninen, Panu; Varis, Juha
Abstract : Press‐formed paperboard food packages were heated and cooled to study the humidity effect on the packages with a series of dimension measurements. The empty packages in the form of trays were pre‐dried or preconditioned before their packing with oatmeal, and heating humidity of the packages was altered to find the optimal storing and heating conditions for improving the dimensional stability of the trays. The dimension measurement results showed aggravated dimensional stability of the trays during the heating and cooling. Pre‐drying and low heating humidity were observed to reduce the impact of the humidity effect on the packages, and the humidity effect was linked to the material moisture content change. The dry storing and heating humidity were concluded to enhance the dimensional stability of the press‐formed paperboard food packages. Use of the dry storing condition was found necessary to mitigate the humidity effect in the heating and cooling of the food packages. Abstract : The dry storing and heating conditions were found to mitigate negative humidity effect on the dimensional stability of press‐formed paperboard food packages. The dimensional changes observed in the packages were larger in cross direction (CD) of the material. The material response was aggravated by a cyclic humidity environment associated with the heating–cooling sequence used in the experiments.